Prognosis of the influence of direct oral anticoagulants on the direct medical expenses in patients with atrial fibrillation - S. V. Malchikova; A. N. Korobeinikova; N. S. Maksimchuk-Kolobova; M. V. Kazakovtseva (Фармакоэкономика, 2020)
Aim. To evaluate clinical-economical effectiveness of direct oral anticoagulants (DOAC) dabigatran, rivaroxaban, and apixaban in comparison with warfarin in atrial fibrillation (AF) therapy.Materials and Methods. Mathematical modeling (tree derivation of solutions) on a temporary 5-year horizon from the medical healthcare system perspective. Methods of clinical-economic analysis: analysis “cost-effectiveness”, “budget impact”, and “the analysis of unseized opportunities”.Results. Total direct costs (DC) were lower by 10.3% when dabigatran was used, by 5.2%, when rivaroxaban was used, and by 10.9%, when apixaban was used in comparison with warfarin. The most significant difference was observed due to different cost of therapy for bleeding complications (in the structure of the costs, it occupied 30-38%). In the group of dabigatran, DC on bleeding complications were lower than in the group of warfarin by 22.0%, in the group of rivaroxaban – by 10.9%, in the group of apixaban – by 36.8%. Besides, in the group of dabigatran, the costs associated with the treatment for ischemic stroke were lower by 28.1% The strategy of the application of DOAC in comparison with warfarin provided more adjusted life years (ALY), complications adjusted life years (CALY), and its lower cost. The application of DOAC saves significant funds. At the same time, the saved funds will provide the purchase of additional modern drugs for patients. The cost-cutting reaches 12% for 5 years and up to 33 patients out of 1000 can receive additional treatment.Conclusion. Due to the prevention of thromboembolic complications in patients that received direct oral anticoagulants, the direct costs can be reduced by 28.1% and due to the prevention of bleeding complications – by 36.8% in comparison with the application of warfarin. Direct oral anticoagulants provide more adjusted life years and complications adjusted life years at a lower cost.